Effect Of High Temperature On Oxidation Behavior Of Superheater Materials Formation Of Protective Oxide Scale - Abdul Wahab, Haziq Mudzakir (Universiti Sains Malaysia, 2018)
The oxidation behaviour of Ni-based superalloy C22 and commercial steel 304 SS were investigated at high temperature 800, 900 and 1000˚C with exposure times 24 h under oxidized atmosphere (air). The microsturucture of C22 and 304 SS was characterized by scanning electron microscope (SEM). The composition and morphologies of oxide scales of the surface were examined by X-ray diffraction (XRD) and SEM combined with energy-dispersive spectroscopy (EDX). The results showed a positive effects of an increased Cr content and continuous and dense oxide scales that formed at 800, 900 and 1000˚C for C22 were composed of Cr₂Oᴣ, CrNi and a small amount of MoO₂ and Fe₂Oᴣ. At 1000˚C, the spallation of oxide scales was occurs for 304 SS as a result of thermal stresses. The oxidized Hastelloy C22 exhibits better oxidation resistance than commercial steel 304 SS as the oxide scale formed a dense with corundum structure.